Effectiveness of child to parent educational package in terms of knowledge among adolescents and practice among their parents regarding household waste disposal methods - Sharma, Anjali; Kumar, Atul; Bala, Kanchan (International Journal of Research in Medical Sciences, 2021)
Background: The clean environment not only promotes good health but also enhances the quality of life. Waste management is one of the most concerning issues among developing countries like India. Poor waste management is harmful not only for our environment but it also affects human health. For many infectious diseases like diarrhea, dengue, flu, cholera, etc. The main cause is improper waste management. The largest part of municipal waste is household/ domestic waste hence, it is important to manage waste at a primary source that it household waste. Methods: A quasi-experimental design with quantitative approach was undertaken for the study. Total 103 adolescents who was studying in 6-12th standard in Government Inter College Badowala, Doiwala Block (Dehradun) and their parents were selected as study participants by using a systematic random sampling technique. For data collection Demographic tools, structured knowledge questionnaire and self-reported practice checklist were administered. Data was collected from 17 December to 30 December, 2019. Data were analyzed using descriptive statistics. Results: The present study revealed that 90.2% of adolescents had average knowledge but it was surprising to note that very less (32%) parents had good practice regarding household waste management. After providing education to adolescents regarding household waste disposal methods there was a significant increase in mean posttest knowledge score (20.84) than the mean pretest knowledge score (13.55) of adolescents. The mean posttest practice score-II (9.17) was higher than mean post-test practice score -I (7.55) after children were educating their parents. There was a significant association of pretest knowledge with the type of house and number of people live in house of adolescents. Conclusions: The study concluded that child to parent educational package is an effective intervention to improve the knowledge of adolescents and the practice of their parents regarding household waste disposal methods.